The Effect of Listening Journal on Speaking Ability - Dian Saputra; Muhaiminah Akib (Qalam : Jurnal Ilmu Kependidikan, 2020)
This study examines the effectiveness of using listening journals to students speaking ability. At this moment, researchers were used the listening journal to facilitate learning how to speak. The researchers tested what the effect of the treatment would be on students' speaking abilities.Â  The participants consist of 11 male and 39 female English education students from the Universitas Muhammadiyah Sorong. Data was gathered using a test to determine the students' speech level. This research was under descriptive quantitative, using a pre-experimental design with a center on the sort of one group pretest-posttest design. The information were displayed by the significance of hypothesis testing which appears that the Sig. (2-tailed) the significance of the report is 0.000 less than the level of value 0.05. Therefore, the null hypothesis was rejected and the alternative hypothesis was accepted. The results showed that there was an impact use of listening journal media on students' speaking skills.